Strategi Mencetak Siswa untuk Siap Menghadapi Era Revolusi Industri 4.0 dan Meningkatkan Semangat Belajar dengan Konsep Law of Attraction bagi Siswa SMA/Sederajat di Lingkungan Mathla’ul Anwar Pandeglang - Henri Henriyan Al Gadri; Asep Sujana; Eka Rosdianwinata (Jurnal Pengabdian Pada Masyarakat, 2019)
STRATEGIES TO STRENGTHEN STUDENTS TO BE READY FOR THE INDUSTRIAL REVOLUTION ERA 4.0 AND INCREASE THE ENTHUSIASM OF LEARNING WITH THE CONCEPT OF LAW OF ATTRACTION FOR HIGH SCHOOL STUDENTS IN MATHLA'UL ANWAR PANDEGLANG. Devotion to this society is attempting to give students through the primary purpose of the workshop about the scored students for ready to face the industrial revolution 4.0 and increase eager to study with the the law of attraction concept. Things that are provided with for students is an understanding of the era of the industrial revolution 4.0, for students, mental maturation an injection motivation, and increase passion for being students who superior. These efforts becomes strategy in preparing students for ready to face the era of the industrial revolution 4.0. Strategies are delivered to students through the concept of the Law of Attraction. The concept was to give effect both mentally, foster self-confidence, mindset, spirit, determination, and an attitude to face something. The objectives of this workshop are: 1) scored students for ready to confront the industrial revolution 4.0; 2) improve the quality of students that are highly competitive; 3) foster the understanding that the knowledge gained can be actualized in the community; 4) fosters an understanding of the use of digital technology and the Internet of things technology to boost productivity and competitiveness of students; 5) enhance the spirit of learning to boost student achievement.